Ergonomic evaluation of low-cost intervention for carpet trimming workers exposed to hand vibration and noise. (March 2019) - Singh, Ashish Kumar; Meena, Makkhan Lal; Chaudhary, Himanshu
The aim of the study was to investigate the occupational use of low-cost intervention for carpet trimming occupation. This study quantifies the effect of hand-arm vibration and noise exposure to loss in hearing threshold among trimming workers. Ten male participants (right handed) involved in carpet trimming volunteered to participate in this interventional experiment. The participants were queried about the usability of prototype handle based on their subjective perception evaluated through the use of scoresheet/questionnaire. Results demonstrated that the handle intervention reduced the total value of root mean square frequency-weighted vibrations by more than 40% when compared with the conventional handle. The workers were exposed to noise levels ranging from 87.2 to 91.8 dB(A) (mean 89.55 dB(A)). They exhibit mild-to-moderate hearing impairment in the frequency range of 3000–6000 Hz. Based on this preliminary work, we have found that prototype handle was effective in curtailing hand-arm vibration. The prototype handle showed a positive effect on the usability ratings. More practical applications should be explored to prevail the combined effect of hand-arm vibration and noise.